2017
DOI: 10.1002/ehf2.12230
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral muscle training with resistance exercise bands in patients with chronic heart failure. Long‐term effects on walking distance and quality of life; a pilot study

Abstract: AimsThis study aimed to describe a method of peripheral muscle training with resistance bands in patients with chronic heart failure (CHF) and to evaluate its effects on the 6 min walk test and quality of life up to 12 months using a home‐based programme.Methods and resultsTwenty‐two patients with stable CHF (19 men and 3 women), mean age 63.2 years (SD 8.1), New York Heart Association class II–III were randomized to individual home‐based training (HT group), or home‐based training with a group‐based start‐up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 32 publications
0
34
0
1
Order By: Relevance
“…Unsupervised, self-regulated interventions may also offer a viable option to increase physical activity levels and to improve cardiovascular health in populations with stable cardiovascular disease or at increased cardiovascular risk. For instance, Lans et al (31) observed that 12 mo of home-based low-intensity resistance exercise was effective in improving exercise capacity and quality of life in patients with chronic heart failure, with improvements observed as early as within 3 mo of implementation. Similarly, 4 mo of unsupervised home exercise was reported to improve cardiovascular risk profile in hypertensive individuals (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unsupervised, self-regulated interventions may also offer a viable option to increase physical activity levels and to improve cardiovascular health in populations with stable cardiovascular disease or at increased cardiovascular risk. For instance, Lans et al (31) observed that 12 mo of home-based low-intensity resistance exercise was effective in improving exercise capacity and quality of life in patients with chronic heart failure, with improvements observed as early as within 3 mo of implementation. Similarly, 4 mo of unsupervised home exercise was reported to improve cardiovascular risk profile in hypertensive individuals (19).…”
mentioning
confidence: 99%
“…Similarly, 4 mo of unsupervised home exercise was reported to improve cardiovascular risk profile in hypertensive individuals (19). Adherence to nonsupervised interventions may be a matter of concern; however, preliminary evidence indicates acceptable adherence levels (ϳ50 -80%) (31), which could be further increased by patient education and enhanced social support alongside the intervention (21). The use of these behavioral strategies is yet to be tested in the context of home-based unsupervised exercise programs in cardiovascular disease populations.…”
mentioning
confidence: 99%
“…The quality of life of patients with CHF is very poor because of many debilitating symptoms, such as shortness of breath, sleep disorder, and frailty. 13 , 14 Moreover, CHF may adversely affect bone metabolism and induce a severe bone loss, 15 increasing susceptibility to fractures and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, several factors can affect patients' participation and adherence in centre-based programs [6]. Home-based training has emerged as a safe, simple, easy to perform and low-cost alternative to centre-based training, as reported by others that have used walking [12,14] and resistance exercise [11,19]. Studies comparing home-based to traditional centre-based programs showed similar benefits on exercise capacity [14,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…There are several home-based programs explored in the literature. Some of them consisted of education, phone calls support, and orientations that can be combined with isolated resistance exercise [11] or with aerobic exercise using walking [12][13][14], cycle ergometer or treadmill [15]. Other home-based programs have combined aerobic and resistance exercise [16,17], some have added telemonitoring to walking [18] and to resistance exercise [19].…”
Section: Introductionmentioning
confidence: 99%